Acute Coronary Stent Thrombosis: A Rare Case Report - Laudari, Shankar; Yadav, Krishna; Yadav, Kamlesh; Yadav, Rachit; Ghimire, Raksha (Journal of National Heart and Lung Society Nepal, 2024)
Coronary stent thrombosis is an uncommon but potentially catastrophic complication of percutaneous coronary intervention, which can result in acute myocardial infarction and often death. The most consistent predictive factors include premature discontinuation of antiplatelet therapy, the extent of coronary disease, and stent number/length. We present a case of acute stent thrombosis in a patient with Acute Myocardial infarction undergoing Coronary Angiolplasty which occured within half an hour of stents placement along with a review of the literature